Plant species-area relationships are determined by evenness, cover and aggregation in drylands worldwide - DeMalach, Niv (Glob Ecol Biogeogr, 2018)
AIM: Species-area relationships (also known as ‘species-area curves’ and ‘species accumulation curves’) represent the relationship between species richness and the area sampled in a given community. These relationships can be used to describe diversity patterns while accounting for the well-known scale-dependence of species richness. Despite their value, their functional form and parameters, as well as their determinants, have barely been investigated in drylands. LOCATION: 171 drylands from all continents except Antarctica. TIME PERIOD: 2006-2013 MAJOR TAXA STUDIED: Perennial plants METHODS: We characterized species-area relationships of plant communities by building accumulation curves describing the expected number of species as a function of the number of sampling units, and later compared the fit of three functions (power-law, logarithmic and Michaelis-Menten). We tested the prediction that the effects of aridity, soil pH on SAR are mediated by vegetation attributes such as evenness, cover, and spatial aggregation. RESULTS: We found that the logarithmic relationship was the most common functional form (c.50%), followed by Michaelis-Menten (c.33%) and power-law (c.17%). Functional form was mainly determined by evenness. Power-law relationships were found mostly under low evenness, logarithmic relationships peaked under intermediate evenness and the Michalis-Menten function increased in frequency with increasing evenness. The SAR parameters approximated by the logarithmic model (‘small-scale richness’ (b(0)) and ‘accumulation coefficient’ (b(1))) were determined by vegetation attributes. Increasing spatial aggregation had a negative effect on the small-scale richness and a positive effect on the accumulation coefficient, while evenness had an opposite effect. In addition, accumulation coefficient was positively affected by cover. Interestingly, aridity decreased small scale richness but did not affect the accumulation coefficient. MAIN CONCLUSIONS: Our findings highlight the role of evenness, spatial aggregation and cover as main drivers of species area relationships in drylands, the Earth’s largest biome.